1994
DOI: 10.1037/0022-0167.41.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Cultural sensitivity in multicultural counseling: A perceptual schema model.

Abstract: A critical review of the multicultural counseling literature revealed 4 limitations of previous conceptualizations of cultural sensitivity. These limitations are definitional variance, inadequate descriptions of indicators of cultural sensitivity, a lack of theoretical grounding, and limitations in measurement and research designs. After these limitations are explored, cultural sensitivity is defined as a distinct perceptual process. A model of cultural sensitivity is proposed that contextualizes the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 45 publications
2
106
0
2
Order By: Relevance
“…Subscale scores range from 0 to 28, and higher scores suggest greater levels of respondent empathy. A review of subscale items indicated that the Empathic Concern and Perspective-Taking subscales corresponded more directly with conceptual definitions of empathy (i.e., Bohort et al, 2002;Ridley & Lingle, 1996), whereas the Fantasy and Personal Distress subscales did not correspond with recognized conceptualizations of empathy (Constantine, 2001;Hayes & Erkis, 2000). Thus, paralleling past research (i.e., Constantine, 2000), the Empathic Concern and Perspective-Taking subscales were the only subscales used for this investigation.…”
Section: Instrumentsmentioning
confidence: 62%
See 1 more Smart Citation
“…Subscale scores range from 0 to 28, and higher scores suggest greater levels of respondent empathy. A review of subscale items indicated that the Empathic Concern and Perspective-Taking subscales corresponded more directly with conceptual definitions of empathy (i.e., Bohort et al, 2002;Ridley & Lingle, 1996), whereas the Fantasy and Personal Distress subscales did not correspond with recognized conceptualizations of empathy (Constantine, 2001;Hayes & Erkis, 2000). Thus, paralleling past research (i.e., Constantine, 2000), the Empathic Concern and Perspective-Taking subscales were the only subscales used for this investigation.…”
Section: Instrumentsmentioning
confidence: 62%
“…Empathy is a foundational disposition in counseling (Bohort, Elliot, Greenberg, & Watson, 2002) and has been found to be one of the most important factors in discriminating effectiveness in therapy (Bohort et al, 2002;Lafferty, Beutler, & Crago, 1989). Empathy is also considered essential to cross-cultural counseling (Ho, 1992;Ridley & Lingle, 1996). It is believed that therapists' expression of empathy in a culturally responsive manner may be a determining factor in culturally diverse clients' perception of therapist cultural sensitivity during assessment and treatment (Fischer, Jome, & Atkinson, 1998).…”
mentioning
confidence: 99%
“…Schema theory has been introduced to explain development in cultural sensitivity (e.g., Ridley et al, 2000;Ridley, Mendoza, Kanitz, Angermeier, & Zenk, 1994). Individuals begin with relatively impoverished schematic representation of an unfamiliar culture or group.…”
Section: What Develops From Multicultural Experience?mentioning
confidence: 99%
“…특히 문화적 공감이란 다른 사람들의 눈과 귀로 세상을 보고 듣는 것을 의미하며, 그들 내부의 문 화를 경험하는 것을 말한다 (Ivey, Ivey, & Simek-Morgan, 1993). 공감 능력은 문화적 역량 습득과 역량을 효과적으로 발휘하기 위해서 선행되어야 하는 것이며 문화적 요인들을 통합시키는 중요한 요소이다 Ridley & Lingle, 1996). • 간호대학생의 일반적 특성 및 문화적 교류 특성을 파악한다.…”
unclassified